2017
DOI: 10.1038/srep42374
|View full text |Cite
|
Sign up to set email alerts
|

Heteroaryldihydropyrimidine (HAP) and Sulfamoylbenzamide (SBA) Inhibit Hepatitis B Virus Replication by Different Molecular Mechanisms

Abstract: Heteroaryldihydropyrimidine (HAP) and sulfamoylbenzamide (SBA) are promising non-nucleos(t)ide HBV replication inhibitors. HAPs are known to promote core protein mis-assembly, but the molecular mechanism of abnormal assembly is still elusive. Likewise, the assembly status of core protein induced by SBA remains unknown. Here we show that SBA, unlike HAP, does not promote core protein mis-assembly. Interestingly, two reference compounds HAP_R01 and SBA_R01 bind to the same pocket at the dimer-dimer interface in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
162
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(175 citation statements)
references
References 40 publications
4
162
0
Order By: Relevance
“…Recently published results show that a compound chemically similar to 4f inhibits replication by disrupting the HBV capsid protein [22]. To determine if our compounds act by this mechanism, HBV capsid formation was monitored by negative-stain electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently published results show that a compound chemically similar to 4f inhibits replication by disrupting the HBV capsid protein [22]. To determine if our compounds act by this mechanism, HBV capsid formation was monitored by negative-stain electron microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…A recent crystal structure revealed the binding site for sulfamoyl-based HBV capsid effectors at the Cp149 chain B-C dimer-dimer interface (Figure 4A) [22]. Chain B formed a “concave” that contributes most protein-ligand interactions while chain C acted as a “lid”.…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structures showed that compounds from the HAP, phenylpropenamide, and sulfamoylbenzamide series target the same hydrophobic pocket located at the core dimer-dimer interface (9, 1214). By binding to the core protein, CAMs accelerate assembly and interfere with pgRNA encapsidation and viral replication in vitro in HBV-replicating cell lines (9, 11, 1517).…”
Section: Introductionmentioning
confidence: 99%
“…All the docked poses found the HAP binding site (Fig. 5B, C, and D), and all have a hydrogen bond with W102, a key interaction that is present in cocrystal structures with capsid assembly modulators (33)(34)(35). BA-38017 and ENAN-34017 were able to find binding poses on wild-type and all of the mutant core proteins, but for Bay 41-4109, only binding poses on wild-type and V124A were reported, with no poses being reported for the V124F and V124W mutations, suggesting that these mutations could prevent binding of Bay 41-4109.…”
mentioning
confidence: 99%
“…While heteroaryldihydropyrimidines (HAPs), such as Bay 41-4109 and GLS4, misdirect capsid assembly to form noncapsid polymers of core proteins (25)(26)(27)(28), all other reported chemotypes of core protein assembly modulators induce the formation of various sizes of capsids devoid of viral pgRNA and DNA polymerase (29)(30)(31)(32). Structural biology studies suggest that HAPs, phenylpropenamides (PPAs), and sulfamoylbenzamides (SBAs) all bind to a hydrophobic pocket formed at the dimer-dimer interface near the C termini of core protein subunits, with contributions from two neighboring core protein dimers (33). Binding of these molecules in the HAP pocket induces large-scale allosteric conformational changes in core protein subunits and results in quaternary and/or tertiary structure changes of capsids (34,35).…”
mentioning
confidence: 99%